Inducting undergraduate medical students via WhatsApp-based multiple mini interviews during COVID-19 pandemic - Aziz, Iqra; Syed Hasan Shoaib; Sundus Iftikhar; Muhammad Zahid Bashir; Akbar Ashraf; Munawar Shahzad (Journal of the Pakistan Medical Association, 2022)
Selection of medical students requires both cognitive and soft skills assessment. Shalamar Medical and Dental College (SMDC) has been using on-campus multiple mini interviews to assess the latter but due to Covid-19 pandemic it became imperative that an alternative be found. The aim of this communication is to share the process SMDC went through to plan, design, and ultimately conduct WhatsApp-based multiple mini interviews (wMMI) in a low risk method as an entry criteria for undergraduate medical students. The process involved designing scenarios appropriate for online interviews, training the faculty members regarding conducting MMI as well as the use of technology, and designing an online webpage for enrolling, scheduling and assessing candidates. We were able to successfully complete wMMI process for 522 candidates within one week in a low risk setting using WhatsApp as communication medium with strong IT and administrative support. Keywords: Medical student; Admission; Selection; Multiple mini interviews;